BIOTECHNICAL SYSTEM FOR MEDICAL PURPOSE CLOSED CONTROL CONTROL - Polishchuk , S. T.; Balabanovich , G. V.; Ivchenko, P. O. (Problems of Informatization and Management, 2021)
The hemodialysis biotechnical system is analyzed, the control device of which is the "artificial kidney" device, the object of control is a patient with impaired renal function. It turns out that modern hemodialysis systems are built on an open control scheme. The structure of the hemodialysis system with a closed control loop is synthesized.